Internet sebagai Ruang Baru Kontestasi Diskursus Agama dan Politik: Kajian atas Diskursus Islam, Demokrasi dan Pancasila pada Website Keislaman Populer di Indonesia - M. Mujibuddin; M. Fakhru Riza (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2021)
The internet as a new medium has now become a contested space for political discourse. Focusing its analysis on eight popular Islamic websites in Indonesia, this paper examines how popular Islamic websites promote the concept of Islam and politic as seen in the issues of Pancasila, democracy, and Islamic state. The required data were collected through the method of web scraping. By using Lutfi Assyaukani's theory of three models of democracy in Indonesia, the results of this study indicate that the selected eight websites were classified into three variants of the political ideology model: First, websites that support religious democracy that are represented by the websites Nu.or.id, Islami.co, Ibtimes.id, and Bincangsyariah.com; second, websites that support Islamic democracy that are represented by Hidayatullah.com and Eramuslim.co.; and third, websites that support the Islamic caliphate that are represented by Voa-Islam.com and Nahimunkar.org, which rejected the form of a democratic state, both Islamic democracy and religious democracy, but accepted the Pancasila version of the Jakarta Charter.